Bullatacin triggers immunogenic cell death of colon cancer cells by activating endoplasmic reticulum chaperones - Fangtian Fan; Peiliang Shen; Yue Ma; Wangbo Ma; Hongyan Wu; Hao Liu; Qing An (BMC, 2021)
Abstract Background It is well accepted that the immune system efficiently contributes to positive outcomes of chemotherapeutic cancer treatment by activating immunogenic cell death (ICD). However, only a limited number of ICD-inducing compounds are well characterized at present; therefore, identification of novel ICD inducers is urgently needed for cancer drug discovery, and the need is becoming increasingly urgent. Methods Herein, we assessed the antitumour activity of bullatacin by MTS assay and apoptosis assay. ICD biomarkers, such as calreticulin (CRT), high-mobility group protein B1 (HMGB-1), heat shock protein (HSP)70, HSP90 and ATP, were assessed by Western blotting, ELISA and flow cytometry. Western blot and qPCR assays were performed to explore the underlying mechanisms of bullatacin-induced ICD. Flow cytometry was used to detect macrophage phagocytosis. Results First, bullatacin induced apoptosis in both SW480 cells and HT-29 cells in a time-dependent manner at 10 nM, as assessed by flow cytometry. Moreover, Western blot and flow cytometry assays showed that CRT and HSP90 (biomarkers of early ICD) significantly accumulated on the cell membrane surface after approximately 6 h of treatment with bullatacin. In addition, ELISAs and Western blot assays showed that the second set of hallmarks required for ICD (HMGB1, HSP70 and HSP90) were released in the conditioned media of both SW480 and HT-29 cells after 36 h of treatment. Furthermore, qPCR and Western blot assays indicated that bullatacin triggered ICD via activation of the endoplasmic reticulum stress (ERS) signalling pathway. Finally, bullatacin promoted macrophage phagocytosis. Conclusion This study documents that bullatacin, a novel ICD inducer, triggers immunogenic tumour cell death by activating ERS even at a relatively low concentration in vitro.